A literature review on the relationship between infertility and sexual dysfunction: Does fun end with baby making?. (August 2014) - Piva, Isabella; Lo Monte, Giuseppe; Graziano, Angela; Marci, Roberto
Abstract Objective To analyse the relationship between infertility and sexuality, and the effect of assisted reproductive technology (ART) on a couple's sexual relationship. Method The literature review is a result of a search that was undertaken with the keywords 'infertility' and 'sexuality' in PubMed from 2000 until 2013. Results Even though abstinence or inadequate sexual activity are often reported in infertile couples, sexual disorders rarely cause infertility. They usually arise, instead, as a result of involuntary childlessness and assisted reproduction. Qualitative studies provide a detailed description of the impact of infertility and its treatment on the couples' sexual relationship, along with its specific gender effects, yet it is difficult to set standardised parameters to quantify sexual strain and the reliability of the studies available is limited by major drawbacks. Conclusions Appropriate measures should be designed to identify sexual disorders in infertile couples, and the medical team should be trained to deal systematically with the couple's sexuality and propose strategies to overcome sexual disturbances. This approach could preserve the quality of the couple's sexual relationship and maximise pregnancy chances in ART. Chinese Abstract 摘 要 目的 分析不育与性功能障碍的关系，以及辅助生育技术（assisted reproductive technology，ART) 对夫妇性关系的影响。 方法 对2000年至2013年之间PubMed上发表带有"不育"和"性欲"关键词的文献进行回顾分析。 结果 虽然经常有不育夫妇禁欲和性活动少的报道，但是性功能障碍很少引起不育。然而，常常情不自禁的无孩子的意识及辅助的生殖会影响性欲。有大量的研究对不育及其治疗对夫妇性关系的影响进行了详细的描述，然而对性活动设定标准的量化参数非常困难，因所收集的研究的存在重要的缺陷。 结论 采取适当的措施查明不育夫妇的性功能障碍，对医疗团队进行培训，对夫妇的性欲进行系统的评估，并采取适当的策略克服性功能障碍。此方法可以对夫妇性关系的质量进行评估，并且对进行ART的夫妇争取最大的怀孕机会。